World War II in the Aleutians: The Fundamentals of Joint Campaigns - Breslin, Charles B. (1994)
This paper is an examination of the Aleutian Campaign conducted by U. S. Armed Forces from June 1942 through August 1943 to gain control of the North Pacific and remove the Japanese from Attu and Kiska Islands. The campaign, characterized by flawed joint operations, involved an extended air operation, an effort for control of the waters of the Western Aleutians, and finally, two major amphibious operations. The Aleutian campaign, studied extensively after August 1943 to apply tactical lessons learned to other theaters, is today a largely ignored theater of operations. Yet, it was America's first effort to fight in a joint theater and contains many insights as to how today's commander should fight in a joint environment. In particular, this paper examines the inability of U.S. Forces to attain unity of command and synchronization of forces in a unified effort to defeat the Japanese. This paper details the American and Japanese strategy followed by an examination of those areas where U.S. commanders failed in applying the fundamentals in developing a joint campaign. From the mistakes of the Aleutian Campaign, we can validate many of the precepts of joint warfighting. World War II in the Aleutians: